The postearthquake stress state on the Tohoku megathrust as constrained by reanalysis of the JFAST breakout data. Issue 16 (26th August 2017) - Brodsky, Emily E.; Saffer, Demian; Fulton, Patrick; Chester, Frederick; Conin, Marianne; Huffman, Katelyn; Moore, J. Casey; Wu, Hung‐Yu
Abstract: The Japan Trench Fast Drilling Project (JFAST) endeavored to establish the stress state on the shallow subduction megathrust that slipped during the M 9 Tohoku earthquake. Borehole breakout data from the drill hole can constrain both the orientation and magnitude of the principal stresses. Here we reanalyze those data to refine our understanding of the stress state on the fault. In particular, we (1) improve the identification of breakouts, (2) consider a fuller range of stress states consistent with the data, and (3) incorporate new and more robust laboratory constraints on rock strength. The original conclusion that the region is in a normal faulting regime after the earthquake is strengthened by the new analysis. The combined analysis suggests that the earthquake released sufficient elastic strain energy to reset the local stress field. Plain Language Summary: The 2011 M 9.0 Tohoku earthquake produced a catastrophic tsunami by moving the seafloor 50 m at the trench. Stress measurements from a borehole that penetrated the fault confirm that this record‐breaking slip appears to have released all of the stress that had been stored at the plate by centuries of plate motion. Prior to the Tohoku earthquake, many scientists believed that each earthquake generally released only part of the stress driving the fault. The stress data presented here quantitatively show that at this locale, the shear stress was entirely released. Key Points: The maximum horizontal stress is 28° from the plate motion suggesting stress changes during the earthquake comparable to the ambient stress All possible solutions of the data require that the system was in a normal faulting regime 14 months after the 2011 Tohoku earthquake Extrapolating the stress state to the fault results in effective friction that is lower averaged during all of slip